Hubungan Nilai Budaya dengan Perilaku Pencegahan Stroke pada Penderita Hipertensi - Ruslang Ruslang; Eka Wulansari; Nurhikmah Wijaya; Alvia Damayanda (Journal Research of Health Administration and Public Health (JRHAPH), 2025)
Stroke is a leading cause of death and disability globally, with hypertension being the most dominant risk factor. Beyond clinical factors, stroke prevention behavior is also influenced by socio-cultural factors. Bugis cultural values such as macca, warani, malempu, and malabo have the potential to shape health behavior; however, empirical evidence examining the relationship between cultural values and stroke prevention behavior among hypertensive patients remains limited. This study aimed to analyze the relationship between cultural values and stroke prevention behavior among patients with hypertension. A quantitative study with a cross-sectional design was conducted in August 2025 in Nepo Village, Tanasitolo District, Wajo Regency. The sample consisted of 30 hypertensive patients selected using purposive sampling. The independent variable was cultural values, while the dependent variable was stroke prevention behavior. Data were collected using a locally based cultural values questionnaire and a stroke prevention behavior questionnaire. Data analysis was performed using univariate and bivariate analysis with a significance level of 0.05. Most respondents had moderate cultural values (46.7%) and moderate stroke prevention behavior (43.3%). Cross-tabulation showed that respondents with high cultural values were predominantly characterized by good stroke prevention behavior (23.3%), while those with low cultural values tended to demonstrate poor prevention behavior (13.3%). Statistical analysis indicated a significant relationship between cultural values and stroke prevention behavior (p = 0.012). Cultural values were significantly associated with stroke prevention behavior among hypertensive patients. Higher cultural values were linked to better stroke prevention behavior. Integrating local cultural values into health promotion interventions has the potential to improve the effectiveness of stroke prevention in a contextual and sustainable manner.